1979
DOI: 10.2307/747430
|View full text |Cite
|
Sign up to set email alerts
|

Effects on Poor Readers' Comprehension of Training in Rapid Decoding

Abstract: Two experiments were designed to examine the effects on comprehension of increasing the decoding speed of poor readers. In the first experiment, poor readers were trained to read a list of words as rapidly as good readers, and then asked to read a passage comprised of the practiced words. Decoding speed measures on the word list and passage and comprehension measures were obtained. The performance of the trained poor readers was compared to their performance on an equivalent untrained passage and to the perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

5
60
2
1

Year Published

1983
1983
2007
2007

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 114 publications
(68 citation statements)
references
References 22 publications
5
60
2
1
Order By: Relevance
“…This effect is apparent in the studies reported by Fleisher et al (1979) and Spring et al (1981) in which unintentional cues to read quickly and accurately may have altered performance and from studies in which cues to change reading performance were intentionally manipulated (DiStefano et al, 1981;Frase & Kreitzberg, 1975;Grant & Hall, 1967;Pehrsson, 1974). Thus, students do not appear to shift their attention to comprehension automatically when reading fluently.…”
mentioning
confidence: 91%
See 3 more Smart Citations
“…This effect is apparent in the studies reported by Fleisher et al (1979) and Spring et al (1981) in which unintentional cues to read quickly and accurately may have altered performance and from studies in which cues to change reading performance were intentionally manipulated (DiStefano et al, 1981;Frase & Kreitzberg, 1975;Grant & Hall, 1967;Pehrsson, 1974). Thus, students do not appear to shift their attention to comprehension automatically when reading fluently.…”
mentioning
confidence: 91%
“…According to the research which has investigated the effects of automatic decoding, little support exists to substantiate the premise that readers automatically attend to comprehension. Studies on training words in isolation have shown definite increases in word recognition rates, but concomitant effects on comprehension have not been reported (Fleisher et al, 1979;Spring et al, 1981). This suggests that students may need to be cued to shift their attention from word recognition to comprehension once fluent reading has been achieved.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…A short-term training program prepared by Fleisher, Jenkins, and Pany (1979) focused specifically on word recognition and not on meaning. Although the training program was successful in increasing the decoding accuracy and speed for fourth-and fifth-grade subjects, no associated gain in comprehension was observed.…”
mentioning
confidence: 99%